Militant Leadership and Terrorism in Armed Conflict - Doctor, Austin C. (Terrorism and political violence, 2024)
The lethality and the frequency of terrorist attacks conducted by militant organizations vary considerably. Some militants perpetrate extreme and systemic levels of terrorist violence, some only do so occasionally, and others never conduct terror operations. To predict group-level differences in this outcome, we draw on conceptual frameworks in the political science and psychology fields to argue that prior military experience shapes leaders’ willingness to engage in terrorist violence. But not all experiences are created equal. We argue that formal experiences such as those associated with military training serve as a restricting influence on terrorist violence, while less formal and less structured experiences such as time in active combat are associated with increases in future terrorist violence. Using new data on the individual backgrounds of militant leaders active between 1989 and 2013, we find support for our hypotheses. This study contributes to the academic literature by bringing the leader back into explanations of wartime terrorist activity. Our findings also carry notable policy implications for policy makers, warfighters, and counterterrorism practitioners.